A turbo SDMA receiver for strongly nonlinearly distorted MC-CDMA signals - Silva, Paulo (2013)
In this paper we consider the use of SDMA (Space Division Multiple Access) techniques for the uplink of MC-CDMA systems (MultiCarrier -Coded Division Multiple Access) where the transmitted signals face strong nonlinear distortion effects. We define an iterative receiver that jointly performs a turbo-MUD (Multiuser Detection) as well as estimation and cancellation of the nonlinear distortion effects.